PI3K-AKT-mTOR Pathway is Dominant over Androgen Receptor Signaling in Prostate Cancer Cells - Mari Kaarbø; Øyvind Løveseter Mikkelsen; Lene Malerød; Su Qu; Viola H. Lobert; Gulcan Akgul; Thomas Halvorsen; Gunhild M. Mælandsmo; Fahri Saatcioglu (Cellular Oncology)
Background: Androgen receptor (AR) and the phosphatidylinositol-3 kinase (PI3K) signaling are two of the most important pathways implicated in prostate cancer. Previous work has shown that there is crosstalk between these two pathways; however, there are conflicting findings and the molecular mechanisms are not clear. Here we studied the AR–PI3K pathway crosstalk in prostate cancer cells in vitro as well as in vivo.